Ultrastructure of Escherichia coli Cells Infected with Bacteriophage R17 - Franklin, Richard M. (1966)
Franklin, Richard M. (Institut de Recherches sur le Cancer, Villejuif, Seine, France), and Nicole Granboulan. Ultrastructure of Escherichia coli cells infected with bacteriophage R17. J. Bacteriol. 91:834–848. 1966—Ultrastructural changes in Escherichia coli cells infected with ribonucleic acid (RNA) bacteriophage R17 were studied under conditions of one-step growth. No morphological alterations were seen during the latent period. During the period of rapid viral synthesis, a fibrillar lesion surrounded by ribonucleoprotein particles was observed in a polar region. Late in infection, paracrystalline arrays of virions were found in over 90% of the cells. When protein synthesis was blocked by in over 90% of the cells. When protein synthesis was blocked by chloramphenicol at 20 min postinfection, allowing continued viral RNA synthesis without production of coat protein, a dense fibrillar area appeared in a paranuclear region. Cytochemical studies were done on cells embedded in hydroxypropyl methacrylate, a water-miscible embedding agent. The paracrystalline arrays of virions were digested after extensive treatment with either pepsin or ribonuclease. Shorter digestion with the pepsin resulted in better definition of the crystal regions. The fibrillar area found in chloramphenicol-treated cells was digested by ribonuclease but not by pepsin, and was also resistant to lead extraction. This region probably represents a pool of virus-specific RNA.